Toxicological Effect of Lauric Acid Based Insecticide on the Reproduction System, Growth Development and Feeding Activity of Aphids, Aphis gossypii Glover - Mat Sarip, Siti Hajar; Aziz, Azila Abdul; Ya'akob, Harisun; Puad, Khalidah (International Journal of Biotechnology for Wellness Industries, 2016)
The toxicological effect of lauric acid based insecticide was investigated in terms of mode of action on aphids target system. Treated leaves were sprayed with different insecticides, which were lauric acid, cinnamaldehyde and malathion at 50µg/ml concentration to compare the effect of the pesticides on reproduction, growth development and feeding activity of aphids. The total number of new born nymphs produced and the relative development stage of nymphs were significantly reduced in all treatments compared to untreated leaves. Number of new born nymphs treated using lauric acid based pesticide was 6.0 ± 1.41 nymphs/day and the growth development rate at second day post treatment was rDS=1.07 ± 0.10. This data showed no significant difference with the data obtained when cinnamaldehyde and malathion were used as positive controls but the results were significantly different from the results obtained using untreated leaves (22.5 ± 3.54 nymphs/day, rDS=1.82 ± 0.02). Lauric acid was also shown to reduce the feeding activity of aphids. The study demonstrated that lauric acid was toxic to aphids. It has the ability to slow down the reproduction system, reduce growth development rate and decrease feeding activity of aphids (Aphis gosyypii Glover).